(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The feasibility of fermented litter as an alternative feed material for ruminant livestock is measured by organoleptic quality, fiber profile, heavy metal contamination, and the presence of worm eggs. This study aimed to examine the influence of broiler chicken litter fermentation with different fermentation lengths on organoleptic quality, and contents of cuprum (Cu), lead (Pb), worm eggs, fiber fractions including hemicellulose, cellulose, neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin, and fermented litter fiber profile through analysis of scanning electron microscope-energy dispersive X-ray (SEM-EDX). Materials and Methods: This study used a complete randomized design of a unidirectional pattern with four treatments and four repeats with long fermentation treatments of 0, 3, 6, and 9 weeks. Result: The results showed a real influence (p ≤ 0.05) of fermentation length on organoleptic quality, NDF, ADF, lignin, hemicellulose, and fiber profile with SEM-EDX observations, with no presence of worm eggs and heavy metal content is still at a safe level for feed materials. Conclusion: This study concluded that the processing of broiler chicken litter with 6 weeks of fermentation gave the best results on organoleptic observations, fiber profile, no presence of worm eggs, and heavy metal contamination that is safe for livestock. J. Adv. Vet. Anim. Res., 8(2): 312-322, June 2021